EXPLORING THE ANTI-INFLAMMATORY PROPERTIES OF METFORMIN IN EXPERIMENTAL HEMORRHOID MODELS - DARMAWI, DARMAWI; HAMIDY, MUHAMMAD YULIS; SORAYA, SORAYA; AZIZAH, NURUL; IRHAM, LALU MUHAMMAD; NOPITASARI, BAIQ LENY; RANGKUTI, INA F.; KASMAN, A. A. MUHAMMAD NUR; ADIKUSUMA, WIRAWAN (International Journal of Applied Pharmaceutics, 2025)
Objective: This study investigated the anti-inflammatory potential of metformin as a therapeutic agent in an experimental hemorrhoid model using Sprague-Dawley rats. Methods: Rats were assigned to six groups: normal control, negative control (hemorrhoid-induced without treatment), positive control (hemorrhoid-induced and treated with aspirin), and three metformin-treated groups receiving 3 mg/kg, 9 mg/kg, and 15 mg/kg body weight doses. Metformin's effects were assessed through macroscopic observation, qPCR analysis of IL-6, TNF-α, IL-10, and COX-2 gene expression, and histopathological examination of leukocyte infiltration and venule diameter. Results: qPCR analysis revealed significant reductions in IL-6 and TNF-α expression in metformin-treated groups compared to the negative control. Specifically, the 9 mg/kg dose achieved a 99% reduction in IL-6 and over 98% reduction in TNF-α expression. COX-2 expression was also significantly decreased in metformin-treated groups (p<0.0001), while IL-10 expression remained unchanged (p=0.3973). Histopathological analysis showed a dose-dependent reduction in leukocyte infiltration, with the 15 mg/kg dose exhibiting the most significant decrease (p<0.0001). Additionally, metformin treatment resulted in a significant reduction in venule diameter, particularly at the 15 mg/kg dose (p<0.0001). Conclusion: These results suggest that metformin, especially at higher doses, has significant anti-inflammatory effects in experimental hemorrhoid models, indicating its potential as a promising therapeutic option for hemorrhoid treatment.